Research on the Evolution of Population Distribution and Influencing Factors in Xi'an During the COVID-19 Epidemic Control Period: Based on a Perspective of Multi-source Spatio-Temporal Big Data. Issue 2 (May 2021) - Zhao, Kaixu; Zhang, Shuaibing; Li, Enlong; Chen, Xiaolan; Wu, Fengqi
Abstract: Under the "ultra-conventional" control measures of the COVID-19 period, urban population distribution is different from usual time. Studying its evolution laws has a certain reference effect for the judgment of urban population aggregations, the division of precise control zoning, and the differentiated management of places during the COVID-19 control period. Based on the data of Baidu heat maps and points of interest (POIs), this paper uses three models of the population density index (PDI), the exploratory spatial data analysis (ESDA) and the geological detector (Geodetector) to analyze the characteristics and the influencing factors of the evolution of population distribution of Xi'an in three stages which are closed control stage, unsealed control stage and slack control stage. The results show that: in the three stages, 1) The value of the PDI and the range of the PDI change in Xi'an continue to increase. The single-day PDI curve shows "low-high-low" changing characteristics from morning to night in and within the third ring zone, and "high-low-high" in the suburb. And, by comparison, it is found that the social vitality of the first and second ring zone is more strongly impacted because of COVID-19 control measures. 2) The overall population density in Xi'an is gradually increasing, this is represented by gradual increase of the very high- and the high-density areas, and continuous decrease of the low- and the very low-density areas. And the centripetal distribution of population density, which is high inside the city and low outside the city, is becoming more and more obvious. 3) The spatial distribution of population density represents obvious high-value clusters or low-value clusters in the three stages, ESDA shows a circle structure of inner heat and outer cold, and this trend continues to be reinforced. 4) The intensity order of influencing factors of the 7 types of facilities on population distribution is: residential communities > catering facilities > living service facilities > healthy facilities > commercial facilities > office places > green spaces and squares, and the influencing factor intensities show a continuous increasing or a continuous decreasing process in the three stages.